An experimental–numerical study on the evolution of the Taylor–Quinney coefficient with plastic deformation in metals. (April 2023) - Dæhli, Lars Edvard Blystad; Johnsen, Joakim; Berstad, Torodd; Børvik, Tore; Hopperstad, Odd Sture
Abstract: When plastic deformation of metals occurs by dislocation motion, a part of the plastic work is stored in the material while the remainder is dissipated as heat. The fraction of the plastic work dissipated as heat can be observed on a macroscopic scale as infrared radiation. Typically, this fraction of plastic work converted into heat is assumed to be constant and around 90%. In this study, an experimental–numerical approach was used to calculate the Taylor–Quinney coefficient as a function of plastic deformation. The experimental foundation was obtained by performing tension tests at slightly elevated strain rates on notched specimens from two dual-phase steels and an aluminium alloy in three temper conditions. The temperature on the surface of the specimens was obtained using an infrared camera, and these temperature recordings were correlated to displacement measurements from a virtual extensometer enabled by digital image correlation. A user material model was used in combination with the thermo-mechanical solver in Abaqus/Standard to perform numerical simulations of the tension tests. Simulations were carried out with both constant and strain-dependent values of the Taylor–Quinney coefficient to examine the effect on the surface temperature in the centre of the specimen during the deformation process. Furthermore, numerical simulations were conducted to find a numerical expression for the Taylor–Quinney coefficient as a function of equivalent plastic strain, such that the temperature evolution in the simulations matches with the temperature measurements from the experiments. Highlights: Evolution of Taylor–Quinney coefficient is estimated for five different materials. A simple, coupled experimental–numerical approach is presented. Taylor–Quinney coefficient tends to increase with plastic strain in all materials. Evolution of Taylor–Quinney coefficient can be correlated with hardening rate.